Analisis Kinerja Keuangan dengan Metode Economic Value Added (EVA) (Studi pada PT. Behin Karya Tahun 2015-2019 ) - Ali Muhajir (JES (Jurnal Ekonomi Syariah), 2020)
This study sample aims to measure the financial performance of PT. Behin Karya in 2015-2019 using the economic value added (EVA) method. This study uses a descriptive method with a quantitative approach. The population in this study is the financial statements of PT. Behin Karya 2015-2019. This study’s sample is the company's financial statements, especially the balance sheet and income statement. The results showed that the overall financial performance of PT. Behin Karya, using the Economic Value Added (EVA) method is excelent, because it has succeeded in achieving a positive value, despite fluctuating. This is because the operating profit generated by the company in 2015-2019 is very high so that it can be compared between the capital charges value and the NOPAT value that the NOPAT value is higher than the capital charges value. Keywords: financial performance; economic value added (EVA)